EXAMİNİNG THE COMPOSİTİON WRİTİNG SKİLLS OF CLASSROOM TEACHER CANDİDATES - İssi, Elif; Bozkurt, Eyüp (Şahin ORUÇ, 2024)
Classroom teachers should be able to pick up the pen and find something to write at any time, anywhere, regardless of the subject. What is expected from the classroom teacher is that it is gaining writing skills, being able to express feelings and thoughts in writing and conveying tüm completely. The aim of this research is to show how accurately and effectively prospective classroom teachers who continue their higher education can apply the composition writing skills they learned in the Turkish Language Teaching course. For this purpose, the student's compositions were evaluated by two different researches in three parts as "format, language and expression, spelling and punctuation" within the scope of Prof. Dr. Cemal Yıldız's "Written Expression Evaluation Form". In this respect, the research is suitable for the case study design, one of the qualitative research methods. The population of the research consists of 58 classroom teacher candidates studying in the second year of a state university in the Eastern Anatolia region. An easily accessible sample was used in the research.

Sınıf öğretmenleri her an, her yerde konu fark etmeksizin kalemi eline alıp yazacak bir şeyler bulabilmelidirler. Sınıf öğretmeninden beklenen; yazma becerisi kazanması, duygu ve düşünceleri yazılı olarak ifade edebilmesi ve bunları eksiksiz aktarabilmesidir. Bu araştırmanın amacı yüksek öğrenimine devam eden Sınıf öğretmeni adaylarının Türkçe Öğretimi dersinde öğrenmiş oldukları kompozisyon yazma becerilerini ne derece doğru ve etkili bir şekilde uygulayabildiklerini göstermektir. Bu amaç doğrultusunda öğrencilerin kompozisyonları Prof. Dr. Cemal Yıldız’ın “Yazılı Anlatımı Değerlendirme Formu” kapsamında “biçim, dil ve anlatım, yazım ve noktalama” olarak 3 kısımda iki farklı araştırmacı tarafından değerlendirilmiştir. Bu yönü ile araştırma nitel araştırma yöntemlerinden durum çalışması desenine uygundur. Araştırmanın evrenini, Doğu Anadolu bölgesindeki bir devlet üniversitesinin 2.sınıfında öğrenim gören 58 Sınıf öğretmeni adayı oluşturmaktadır. Araştırmada kolay ulaşılabilir örneklem kullanılmıştır.
SINIF ÖĞRETMENİ ADAYLARININ KOMPOZİSYON YAZMA BECERİLERİNİN İNCELENMESİ
Keywords: Other Fields of Education (Other); Alan Eğitimleri (Diğer)